American life writing and the medical humanities : writing contagion - Allen Wright, Samantha (Bingley, U.K. : Emerald Publishing Limited, 2020)
American Life Writing and the Medical Humanities: Writing Contagion bridges a gap in the market by linking the medical humanities with disability studies. It examines how Americans have used life writing to record epidemic disease throughout history. Starting in the late 1800s with Yellow Fever and ending with the 2014-2016 Ebola outbreaks, the author tracks how American life writing changed literature, history, and medicine. Although the illness narrative genre became more popular in the mid-20th century, Americans have been writing illness narratives throughout American history. Writing Contagion focuses on American epidemics to see how these outbreaks spurred Americans into telling their stories. Looking at book-length narratives of illness and disability, the author traces the development and lineage of illness narratives from early American nonfiction writing, to literary modernism and to contemporary memoir. Viewing illness narratives as intensely interdisciplinary, the author argues that to understand both the importance and influence of this genre within American literature, illness narratives need to be read through literary, disability studies, and medical humanities frameworks to challenge ableist assumptions and demonstrate how illness narratives are of both historical and literary importance in America.
Includes bibliographical references and index.
Print version record.
Keywords: Autobiography; Biography; Communicable diseases -- United States; Biography & autobiography -- General; Memoirs